2009
DOI: 10.1002/elan.200804563
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer‐Based Electrochemical Sensor for Label‐Free Recognition and Detection of Cancer Cells

Abstract: An electrochemical biosensor was developed for the label-free and selective detection of leukemia cells based on aptamer-modified gold electrode using electrochemical impedance spectroscopy (EIS) technique. The thiolterminated aptamer (sgc8c) selected for CCRF-CEM acute leukemia cells was self-assembled onto the gold electrode surface as recognition probe, which was characterized by cyclic voltammetry (CV) and EIS using Fe(CN) 6 3À/4À as a redox probe. The surface density of aptamers was determined by chronoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(50 citation statements)
references
References 34 publications
2
48
0
Order By: Relevance
“…Meanwhile, the results of the control experiments revealed that this method also displayed a considerable selectivity. Furthermore, the detection limits of recent reports were in a level of 1 × 10 3 cells (He et al, 2009;Pan et al, 2009); benefiting from the DNAzyme-linked amplification, we were able to detect cancer cells in 1 × 10 2 level.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…Meanwhile, the results of the control experiments revealed that this method also displayed a considerable selectivity. Furthermore, the detection limits of recent reports were in a level of 1 × 10 3 cells (He et al, 2009;Pan et al, 2009); benefiting from the DNAzyme-linked amplification, we were able to detect cancer cells in 1 × 10 2 level.…”
Section: Resultsmentioning
confidence: 74%
“…Recently, Herr et al (2006) made use of aptamer to target cancer cells. From then on, a variety of aptamer-based assays for cancer cells have been developed with different measuring techniques, including fluorescence , colorimetry (Herr et al, 2006;Smith et al, 2007;Medley et al, 2008) and electrochemistry (Pan et al, 2009). These efforts provide a novel concept for the early cancer diagnosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since their discovery in the 1990s [78], aptamers have been developed as specific, high-affinity probes for bioanalytical and cancer-related research. Aptamers can be chemically conjugated with various signal-generating components for acoustic [79][80][81], electrochemical [82][83][84][85], and optical [86][87][88] sensing. The high affinity, easy fabrication, low cost, and easy modification of aptamers have made them excellent components in DNA hydrogel engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the existing antibodies are quite limited and their preparation is very complex. In order to overcome these limits, some ligand binding molecules, such as aptamers and lectins, were recently discovered, and more recently, oligonucleotides tethered with target-binding small molecules were considered because the small molecule moiety at the terminal of the oligonucleotides can exhibit reasonable affinity and selectivity towards target molecules [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%